OzFoodNet quarterly report, 1 April to 30 June 2008 - OzFoodNet Working Group; Leslie, Katrina (Communicable Diseases Intelligence, 2008)
The Australian Government Department of Health and Ageing established the OzFoodNet network in 2000 to collaborate nationally to investigate foodborne disease. OzFoodNet conducts studies on the burden of illness and coordinates national investigations into outbreaks of foodborne disease. This quarterly report documents investigations of outbreaks of gastrointestinal illness and clusters of disease potentially related to food, occurring in Australia from 1 April to 30 June 2008.